2020
DOI: 10.1002/ece3.6698
|View full text |Cite
|
Sign up to set email alerts
|

Are there phylogenetic differences in salivary tannin‐binding proteins between browsers and grazers, and ruminants and hindgut fermenters?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 117 publications
(211 reference statements)
0
13
0
Order By: Relevance
“…The neutralizing effect of proline-rich protein in saliva has long-been hypothesized ( 102 ). Many browsing herbivores that readily consume tannins do not produce saliva that contains proline ( 103 ). Despite a lack of proline, some browsing ruminants (i.e., goats) can bind tannins with salivary proteins ( 104 ), suggesting that proline is not a requisite for all salivary protein-tannin interactions.…”
Section: Polyphenolicsmentioning
confidence: 99%
“…The neutralizing effect of proline-rich protein in saliva has long-been hypothesized ( 102 ). Many browsing herbivores that readily consume tannins do not produce saliva that contains proline ( 103 ). Despite a lack of proline, some browsing ruminants (i.e., goats) can bind tannins with salivary proteins ( 104 ), suggesting that proline is not a requisite for all salivary protein-tannin interactions.…”
Section: Polyphenolicsmentioning
confidence: 99%
“…We found that some Quercus species, such as Q. alba and Q. michauxii, increased condensed tannin production relative to the amount of tissue removed (Figure 5). We note that many studies have found defenses are induced by specific salivary enzymes and proteins (Berman, 2002;Rooke, 2003;Ward et al, 2020). However, herbivore saliva does not always induce these defenses (Keefover-Ring et al, 2015), and defenses are often induced without such catalysts (Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Salivary tannin-binding proteins are considered the reason for the high protein content of the saliva of such ruminants (Hofmann et al, 2008), and there is a certain relationship between salivary gland size and indicators of homogenous rumen contents (such as a low SF) (Ehrlich et al, 2019;Przybyło et al, 2019). However, as mentioned in the introduction, greater kudu are reported to have particularly small salivary glands (Robbins et al, 1995), to be susceptible to negative effects of tannins (Van Hoven, 1991), and do not have prominent salivary tannin-binding proteins (Ward et al, 2020). These findings are at odds with those of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of expected correlation between the proportion of grass in the natural diet and salivary gland size or masseter mass was later confirmed for the Tragelaphini (Clauss et al, 2008;Hofmann et al, 2008). For greater kudu, a suspected susceptibility to tannin-induced digestive problems that would speak for comparatively low salivary tannin-binding proteins (Van Hoven, 1991), the reportedly small salivary glands (Robbins et al, 1995), a very low magnitude of salivary tannin binding (Ward et al, 2020), and a relatively distinct difference in the papillation of the dorsal as compared to the middle rumen (Clauss et al, 2009b) would all suggest that kudu saliva is not very protein-rich, hence not very viscous, and that therefore rumen contents might show a higher degree of stratification (as reflected in the papillation pattern). This would lead to the prediction of a 'cattle-type' physiology as observed in the Tragelaphini nyala, bongo (T. eurycerus) and sitatunga (T. spekii).…”
Section: Introductionmentioning
confidence: 95%